Characterization and Chemical Composition of Particulate Matter (PM₂.₅) in Selected Rural, Sub-Urban and Urban Area - Kee, Yang Ling (2013)
PM₂.₅ particles can be easily inhaled and deposited into the deeper part of alveoli. Recent epidemiological study has shown that exposure to particulate matter can worsen the condition of chronic respiratory and cardiovascular disease. This study was conducted in three different sites in Malaysia located at rural area (Tasik Chini), sub-urban area (UKM Bangi) and urban area (UKM KL). Total of 26 samples were collected from December 2012 to March 2013 from these sites. Ion chromatography (IC) and inductively coupled plasma mass spectrometry (ICPMS) were used for determining target chemicals in PM₂.₅ IC was used for determining anion such as CI⁻, SO₄²⁻, PO₄³⁻ and NO³⁻. ICPMS was used to determine cation and water soluble trace elements such as Ca²⁺, K⁺, Mg²⁺, Na⁺, Ba, Cd, Cu, Ga, Ni, Pb, Sr and Zn. Concentration of PM₂.₅ at urban area was significantly higher than rural area and sub-urban area. Higher traffic density, high population movement and small scale industries at urban area might be the reason for high concentration of PM2.5. The composition of anion in PM₂.₅ was dominated by SO₄²⁻, followed by NO³⁻, PO₄³⁻ and CI⁻. The composition of cation in PM₂.₅ was dominated by Na+, followed by K⁺, Ca²⁺ and Mg²⁺ at sub-urban and urban area. The concentration of water soluble trace elements in PM₂.₅ was dominated by Zn, followed by Pb, Cu, Ba, Ni, Sr, Cd, and Ga. The concentration of Pb, Cu, and Ba were each found almost double at sub-urban area compared to rural area and urban area compared to sub-urban area. There are very few researches conducted on PM₂.₅ in Malaysia. The scarcity of data on PM₂.₅ is the main problem for establishing PM₂.₅ recommended guidelines in Malaysia. Therefore, the present study will help to provide the quantitative measurements of PM₂.₅ which will help to assess the air quality in Malaysia.